Parents' drinking, childhood hangover? Parental alcohol use, subjective health complaints and perceived stress among Swedish adolescents aged 10-18 years - Joakim Wahlström; Charlotta Magnusson; Sara Brolin Låftman; Johan Svensson (BMC, 2023)
Abstract Background Alcohol abuse is not only harmful to the consumer but may also negatively impact individuals in the drinker's social environment. Alcohol's harm to others is vital to consider when calculating the true societal cost of alcohol use. Children of parents who have alcohol use disorder tend to have an elevated risk of negative outcomes regarding, e.g., health, education, and social relationships. Research on the general youth population has established a link between parental drinking and offspring alcohol use. However, there is a lack of knowledge regarding other outcomes, such as health. The current study aimed to investigate the associations between parental drinking and children's psychological and somatic complaints, and perceived stress. Methods Data were derived from a nationally representative sample, obtained from the 2010 Swedish Level-of-Living survey (LNU). Parents and adolescents (ages 10-18) living in the same households were interviewed independently. The final study sample included 909 adolescents from 629 households. The three outcomes, psychological and somatic complaints and perceived stress, were derived from adolescents' self-reports. Parents' self-reports of alcohol use, both frequency and quantity, were used to categorise adolescents as having abstaining, low-consuming, moderate-drinking, or heavy-drinking parents. Control variables included adolescents' gender, age, family structure, and household socioeconomic status. Linear and binary logistic regression analyses were performed. Results Parental heavy drinking was more common among adolescents living in more socioeconomically advantaged households and among adolescents living with two custodial parents or in reconstituted families. Adolescents with heavy-drinking parents reported higher levels of psychological and somatic complaints and had an increased likelihood of reporting stress, compared with those having moderate-drinking parents. These associations remained statistically significant when adjusting for all control variables. Conclusion The current study's results show that parental alcohol consumption is associated with poorer offspring adolescent health. Public health policies that aim to reduce parental drinking or provide support to these adolescents may be beneficial. Further studies investigating the health-related outcomes among young people living with heavy-drinking parents in the general population are needed to gain more knowledge about these individuals and to implement adequate public health measures.